Assessing the Impact of Parent-Teacher Collaboration on Children's Health Outcomes in Government Primary Schools of Puducherry - Vasanthy, S.; Angeline, Kripa (Journal of Neonatal Surgery, 2025)
Background: Parent-teacher collaboration is widely recognized as a key factor influencing not only children’s academic success but also their health and well-being, especially in settings where health issues such as dental problems, skin diseases, and nutritional deficiencies are prevalent among schoolchildren. Despite its importance, there remains a notable gap in research specifically addressing the impact of structured parent-teacher collaboration programs on children’s health awareness and behavior within government primary schools in India. This study was designed to bridge this gap by evaluating the effectiveness of a targeted collaboration program in improving children’s health outcomes in Puducherry. Methods: The research employed a quasi-experimental design involving 240 participants, equally divided into experimental and control groups, selected through simple random sampling from government primary schools. The experimental group received a structured parent-teacher collaboration intervention, including training sessions on communication, collaboration, and health promotion, while the control group continued standard practices until the intervention was offered post-assessment. Data were collected using validated tools such as the Parent-Teacher Collaboration Scale and the Children’s Health Awareness and Behavior Questionnaire, with assessments conducted at baseline and post-intervention. Ethical clearance was obtained, and informed consent was ensured throughout the study. Results: Post-intervention, the experimental group demonstrated significant improvements in both collaboration levels and children’s health awareness. High collaboration increased from 16.7% to 41.7% in the experimental group (p < 0.001), and good health awareness rose from 33.3% to 58.3% (p < 0.001), both significantly higher than in the control group. Correlation analysis revealed a strong positive relationship between parent-teacher collaboration and health awareness (r = 0.65, p < 0.001) in the experimental group. Conclusion: The findings indicate that structured parent-teacher collaboration programs can effectively enhance collaboration and improve children’s health awareness in government primary schools. The study recommends the implementation of such programs, ongoing teacher training, and further research to assess long-term impacts on child health outcomes